Pengaruh Kepemimpinan, Kompetensi dan Motivasi Terhadap Perlindungan Anak Melalui Kebijakan Pemerintah Pada Dinas Sosial Kota Makassar - Andi Ulvayanti; Mahfudnurnajamuddin; Ramlawati (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Leadership, competence, and motivation are key aspects that greatly influence government policies in child protection that are strategic in the efforts of the government and related institutions to protect the rights and welfare of children, especially at the operational level such as social services or child protection institutions. This study aims to analyze the direct and indirect influence of leadership, competence and motivation on child protection through government policies. The study was conducted at the Makassar City Social Service, using a quantitative approach. The data collection technique (instrument) used was a survey and questionnaire. The population and sample used full sampling of 107 respondents. Data analysis consisted of validity testing consisting of Confirmatory Factor Analysis (CFA), Convergent Valdity, Average Variance Extracted (AVE), Discriminant Validity and reliability testing. Furthermore, quantitative analysis using Partial Least Square (PLS). The results of the study found that the variables of leadership, competence, and motivation directly had a positive and significant effect on government policies and child protection. Furthermore, indirectly the variables of leadership, competence, and motivation had a positive and significant effect on child protection through government policies.